The Influence of Visual Content and Brand Awareness on Enhancing Brand Image on PT Adidaya Multikreasi nstagram Account - Zakian Zakian; Erwansyah Erwansyah; Husni Muharram Ritonga (Journal of Management, Economic, and Accounting, 2026)
The development of social media, particularly Instagram, has transformed it into a strategic platform for visual-based digital marketing. High-quality and consistent visual content plays a crucial role in increasing audience engagement, building Brand Awareness, and forming a positive Brand Image. PT Adidaya Multikreasi, a local retail brand, has shifted its market segmentation from individual consumers (B2C) to the HORECA (Hotel, Restaurant, and Café) industry, which requires adjustments in digital marketing communication strategies. However, pre-survey results indicate that the levels of Brand Awareness and Brand Image of PT Adidaya Multikreasi remain relatively low, especially in terms of visual quality, brand identity consistency, and clarity of product information on the company’s Instagram account. Therefore, this study aims to analyze the influence of visual content and Brand Awareness on Brand Image on PT Adidaya Multikreasi’s Instagram account. The findings of this study are expected to contribute to the development of more effective, relevant, and audience-oriented visual content and digital marketing communication strategies for the HORECA sector.